The results of Femto-LASIK in the correction of hypermetropia and evaluation of patient satisfaction with the effect obtained - T. N. Frolova; L. S. Khlebnikova (Acta Biomedica Scientifica, 2025)
Difficulties in correcting hypermetropia and predicting the refractive effect require an optimal choice of correction of medium and high degree hyperopia. At the same time, it is also important for the patient to adapt to the new quality of vision. The aim. To perform a comparative analysis of refractive indices, optical aberrations and retinal visual acuity in patients after Femto-LASIK for hyperopia correction in groups with subjective satisfaction and dissatisfaction with the result obtained. Materials and methods. The study included 68 patients aged 18 to 37 years (27.52 ± 7.3) with moderate to high degree hypermetropia. All patients underwent a standard ophthalmological examination. The assessment of changes in visual functions was carried out before surgery, a day later, 1 and 12 months after surgery. The degree of subjective satisfaction was assessed by using tests of the quality of vision and asthenopic complaints. The severity of asthenopic complaints was determined using the questionnaire “Symptoms of asthenopia with insufficient convergence”. The results were processed using standard methods using Statistica10 programs. Results. In the postoperative period, vision improved in all patients (Strehl coefficient increased by 4 times, visocontrastometry by 2 times, reduction of aberrations of the lens, cornea and the entire optical system of the eye by 3 times). The survey showed an increase in the quality of vision by 3 times, the symptoms of asthenopia decreased by 2 times. 14 patients (20 %) were dissatisfied with the result. The age of these patients was 5.2 ± 0.61 years higher than the age of satisfied patients. Conclusion. Femto-LASIK is highly effective in correcting moderate and high degree hypermetropia in combination with astigmatism in 83 % of cases. Dissatisfaction with the obtained result was observed when the refractive effect shifted towards myopia, as well as in patients over 30 years of age.